Knowledge discovery, knowledge engineering and knowledge management : 6th International Joint Conference, IC3K 2014, Rome, Italy, October 21-24, 2014, revised selected papers /: 6th International Joint Conference, IC3K 2014, Rome, Italy, October 21-24, 2014, revised selected papers. (2015) - Unknown
No abstract available